Pipe jacking in Singapore : a state-of-the-art trenchless construction technology - Ho, Chin Heng. (2008)
This report aims at a better understanding of the pipe jacking technology with the hope of using the knowledge gained from this understanding to enhance the use of this state-of-the-art trenchless construction technique locally.